2017
DOI: 10.1007/s12298-017-0427-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among mulberry genotypes from seven countries

Abstract: Mulberry (Morus alba) is an economically and ecologically important, widespread woody plant. It has served human beings for over hundreds of years, and it is still widely used in pharmaceuticals, food industry and farming nowadays. Using modern techniques, deeper understanding in classification and conservation resources of mulberry leads to higher-efficiency hybrids among populations. Genetic polymorphisms among 42 mulberry genotypes from seven countries over Asia and South America were detected using 17 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…This indicated that there might exist a connection between cucumber genotype and resistance level against damping-off. The present findings confirmed previous studies demonstrating association between molecular marker clusters and disease resistance response [13,30,43].…”
Section: Clustering and Principal Component Analysissupporting
confidence: 93%
“…This indicated that there might exist a connection between cucumber genotype and resistance level against damping-off. The present findings confirmed previous studies demonstrating association between molecular marker clusters and disease resistance response [13,30,43].…”
Section: Clustering and Principal Component Analysissupporting
confidence: 93%
“…Edible fruits express the number of species and numerous genotypes, accessions, types, and so forth occurring in most of the parts of the world. They accepted one of the most important plant genetic resources and elements of biodiversity [1]. The Chinese dwarf cherry (Cerasus humilis (Bge.)…”
Section: Introductionmentioning
confidence: 99%
“…This difference could be explained by the fact that the samples were collected from individual trees dispersed in distant areas from Latakia. The high level of genetic similarity between M. nigra genotypes was also observed in the study of Wang et al (2017), where low diversity among 42 mulberry genotypes was revealed using 17 ISSR primers (average of Nei's and Shannon's information index 0.116 and 0.174, respectively).…”
Section: Genetic Distance and Genetic Diversity Between And Within Mo...mentioning
confidence: 53%